Influencia del tipo de fibras y del tratamiento superficial de las fibras en las propiedades físicas y mecánicas de compuestos reforzados con fibras vegetales - Sánchez-Cruz, Martha Lissette; Capote Rodriguez, Gil; Patiño-Quiazua, Juan Pablo (Ingeniería, 2023)
Context: The concern for mitigating the environmental impact generated by the use of synthetic fibers as reinforcement of traditional composite materials has promoted the design and characterization of composites made from the combination of materials of plant origin. However, despite its multiple advantages, for its efficient use as construction materials it is necessary to deepen the determination of the effect of design parameters on its mechanical performance. Method: The objective of this study is to determine the effect of the design parameters (type of fibers and surface treatment on the physical and mechanical properties of panels made with materials (fibers and resin) of plant origin. For the elaboration of the composite, two types of fibers were used: Arundo Dónax fibers and Guadua Angustifolia Kunth fibers. To produce the panels, the fibers were randomly distributed in a vegetable resin, obtained from the processing of castor oil. To evaluate the effect of the treatment on the properties of the composite three conditions were considered: fibers without treatment, fibers treated with sodium hydroxide solution and fibers treated with plasma. The density in anhydrous state, the effective absorption capacity, the surface absorption, the swelling percentage, the breaking modulus, and the apparent elastic modulus were determined experimentally. From the experimental results, an analysis of the response surface was carried out through the implementation of a central compound design, using a commercial software. Results: From the experimental results an analysis of the response surface was carried out. Pareto diagrams and contour graphs were obtained for each of the properties studied. From the statistical results it was possible to establish equations that allow predicting the properties of the compound based on the type of fiber and the treatment applied to its surface. Conclusions: From the results, it was possible to verify the effect of the type of fibers and their surface modification on the physical properties of compounds made with materials of plant origin. Other parameters such as orientation of the fibers, as well as variables associated with the processing conditions (pressure and compaction time) can influence the properties of the material) and will be evaluated in future works